Improvement in the performance of low temperature H2–O2 fuel cell with chitosan–phosphotungstic acid composite membranes. (22nd March 2016) - Santamaria, M.; Pecoraro, C.M.; Di Franco, F.; Di Quarto, F.; Gatto, I.; Saccà, A.
Abstract: Free-standing chitosan/phosphotungstic acid polyelectrolyte membranes, prepared by ionotropic gelation on alumina porous supports, were employed as proton conductor in low temperature H2 –O2 fuel cell. A drying step on glass substrate was introduced in the fabrication procedure to reduce shrinkage and consequent corrugation. Membranes were tested with electrodes prepared according to different procedures and with two different Pt loadings, namely 0.5 and 1 mg cm −2 . Both the investigated kinds of electrodes allowed to get very promising power peaks of 550 mW cm −2 in spite of the different Pt content. The polarization curves and the electrochemical impedance spectra suggest that water management is crucial in determining the overall cell performance.